1995
DOI: 10.1080/00140139508925225
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant driving behaviour: errors and violations

Abstract: The present study was a replication of the research of Reason et al. (1990). Its aim was to confirm the distinction between driving errors and violations in a Western Australian driving population. Sixty-one male drivers and 74 female drivers completed a questionnaire containing items on driver demographics, driving penalties incurred, driving convictions and accident history and driver behavioral aberrations drawn from the Driver Behaviour Questionnaire (DBQ). In agreement with Reason et al. factor analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
88
3
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(120 citation statements)
references
References 2 publications
18
88
3
4
Order By: Relevance
“…However, Reason et al's study (1990) did not find such a structure, but found a three-factor structure instead. Other previous studies have also found different factor structures of the DBQ (Blockey & Hartley, 1995;Lawton et al, 1997;Reason et al, 1990;Åberg & Rimmö, 1998). This is not surprising as the driving style is formed by personal factors such as age, gender and cognitive biases, as well as by the social context (Reason 1990;Reason et al, 1990).…”
Section: The Danish Dbq Factor Modelmentioning
confidence: 70%
See 3 more Smart Citations
“…However, Reason et al's study (1990) did not find such a structure, but found a three-factor structure instead. Other previous studies have also found different factor structures of the DBQ (Blockey & Hartley, 1995;Lawton et al, 1997;Reason et al, 1990;Åberg & Rimmö, 1998). This is not surprising as the driving style is formed by personal factors such as age, gender and cognitive biases, as well as by the social context (Reason 1990;Reason et al, 1990).…”
Section: The Danish Dbq Factor Modelmentioning
confidence: 70%
“…Similar results have been obtained in Australia by Lawton et al (1997) and Davey et al (2007) who found support for errors, highway-code violations and interpersonal aggressive violations. However, also within Australian drivers Blockey and Hartley (1995) found a different factor structure consisting of general errors, dangerous errors and dangerous violations in their DBQ study.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Definitely, the number of handicapped and casualties of traffic accidents is 10 to 15 times greater than the number of the related mortalities with its irreparable consequences such as getting helpless without any support, the mental and psychological problems, the extremely back-breaking therapeutic expenses, and also the penal and judicial issues. Many dangerous road accidents happen yearly in Iran pushing many people towards death and subsequently, leaving many families helpless without any support [15]. More than 90% of mortalities occur in low-income and moderate-income countries in Africa and Middle East.…”
Section: Discussionmentioning
confidence: 99%